A study of the critical thinking influences, the big five personality traits, and motivation factors on university students' liberal course achievement - Zhao Jing Yi; Soon Singh Bikar Singh; Huang Chang Li; Ibnis Shaid Abdul Rajun; Zhao Han Yu (Conscientia Beam, 2025)
The study explores the impact of critical thinking, the Big Five personality traits, and motivation on undergraduate achievement in liberal courses. A quantitative survey design was employed, involving 400 undergraduate students from a renowned university in China. The data were analyzed manually using SPSS version 25 software. The results revealed that critical thinking did not significantly affect students' achievement in liberal courses. Similarly, no significant relationship was found between the Big Five personality traits and students' performance. However, a statistically positive relationship was found between personality traits and motivation, suggesting these factors may contribute to improving student outcomes in liberal courses. The Big Five personality traits and motivation approach significantly play a role in enhancing student performance, while critical thinking alone does not directly influence liberal course achievement. The study’s findings are valuable for curriculum developers, educators, and academic leaders in higher education. Institutions can better support student success and optimize teaching strategies in liberal education by understanding the interplay between personality, motivation, and academic performance.